2011
DOI: 10.1007/s13157-011-0184-5
|View full text |Cite
|
Sign up to set email alerts
|

Using Geographic Information Systems (GIS) to Inventory Coastal Prairie Wetlands Along the Upper Gulf Coast, Texas

Abstract: This study developed a Geographic Information System (GIS) framework using datasets such as light detection and ranging (lidar) data, soils, and land use/land cover for analyzing distribution and structure of over 10,000 coastal prairie wetlands (CPWs) around Galveston Bay, Texas, USA. Lidar data were used to estimate volumes and catchment areas. The CPWs were small (median 0.37 ha) with 72% of wetlands less than 1 ha in size. However, CPWs and their catchments occupy 40.8% of the land area within the study ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…subsp. occidentalis) cover (Davies et al 2010), and inventory of coastal prairie wetlands (Enwright et al 2011). Although we demonstrated that NAIP images could be used to map mesquite cover, the results obtained here might not apply to other species, plant communities and/or seasons.…”
Section: Discussionmentioning
confidence: 99%
“…subsp. occidentalis) cover (Davies et al 2010), and inventory of coastal prairie wetlands (Enwright et al 2011). Although we demonstrated that NAIP images could be used to map mesquite cover, the results obtained here might not apply to other species, plant communities and/or seasons.…”
Section: Discussionmentioning
confidence: 99%
“…We generated a normalized difference vegetation index (NDVI) from the August 2009 National Agriculture Imagery Program (NAIP) 1-m resolution color aerial imagery (USDA 2009; see Enwright et al 2011) and rescaled this to 30-m resolution. NDVI is a measure of surface greenness, generally correlating well with live green vegetation and aboveground biomass.…”
Section: Spatial Predictor Variablesmentioning
confidence: 99%
“…If there has been a large disturbance event between the two dates, the data should be used with caution. For instance, LiDAR data collected prior to a hurricane or tropical storm may be less useful because storm events can cause extreme erosion, deposition, and damage to vegetation (Enwright et al 2011). Other natural disturbances, such as wildfires, avalanches, mudslides, or beaver activity, may increase or decrease wetland area (Environmental Laboratory 1987), making older LiDAR datasets obsolete.…”
Section: Discussionmentioning
confidence: 99%